Hematological Parameters in Individuals with Beta Thalassemia Trait in South Sumatra, Indonesia - Dian Puspita Sari; Pustika Amalia Wahidiyat; Iswari Setianingsih; Ina S. Timan; Djajadiman Gatot; Aria Kekalih (Anemia)
Background. β-Thalassemia has a very wide clinical variation, depending on the severity of the patient’s condition. Individuals with β-thalassemia traits are usually asymptomatic; however, laboratory examination will show mild anemia with microcytic hypochromic erythrocytes morphology with wide variation depending on the genotype. This study was conducted to determine the reference value of hematological parameters and hemoglobin (Hb) analysis based on the phenotype of β-thalassemia (β0 and β+) and determine the differences of hematological characteristics between the two phenotypes. Methods. This cross-sectional study was conducted by evaluating the hematological parameters and Hb analysis of the β-thalassemia trait in the family of thalassemia patient population. The subjects were divided into β0 and β+. The subject with normal Hb analysis with or without iron deficiency was excluded. Results. A total of 203 subjects with thalassemia traits were included from the families of thalassemia patients, consisting of 101 subjects with β0-thalassemia, 82 subjects with β+-thalassemia, and the mutation had not been found in 20 subjects. There was a relationship in the mean/median of hematological parameters, HbA2 and HbF, between β0-thalassemia and β+-thalassemia (P<0.05). ROC for each hematological parameter, HbA2 and HbF, showed that the highest diagnostic value based on the area under the curve was mean corpuscular hemoglobin (MCH) (0.900) and mean corpuscular volume (MCV) (0.898). The cutoff point of MCH for β0-thalassemia trait was ≤20.5 pg (sensitivity 85%, specificity 90%) and MCV was ≤66.8 fL (sensitivity 87%, specificity 87%). Conclusion. MCH values can be used as a screening tool for predicting β0-thalassemia in the relatives of thalassemia patients in the South Sumatra population.